Designer antigens for elicitation of broadly neutralizing antibodies against HIV. Issue 9 (26th September 2014) - Kok, Tuckweng; Gaeguta, Adriana; Finnie, John; Gorry, Paul R; Churchill, Melissa; Li, Peng
Abstract : Broadly neutralizing antibodies (bNAbs) are a consistent protective immune correlate in human immunodeficiency virus (HIV) patients as well as in passive immunotherapy studies. The inability to elicit bNAbs is the core reason underlining the repeated failures in traditional HIV vaccine research. Rare monoclonal bNAbs against HIV, however, have been produced. The significance of producing and studying more monoclonal bNAbs against HIV is underlined by its capability of defining critical epitopes for antigen designs aimed at the development of a serum‐neutralizing HIV vaccine. In this regard, traditional antigen preparations have failed. There is a need to clearly advocate the concept, and systematic study, of more sophisticated 'designer antigens' (DAGs), which carry epitopes that can lead to the elicitation of bNAbs. Using an extremely efficient cell‐to‐cell HIV infection model for the preparation of HIV prefusion intermediates, we have investigated a novel and systematic approach to produce (not screen for) potential bNAbs against HIV. We have established the concept and the experimental system for producing formaldehyde‐fixed HIV DAGs that carry temperature‐arrested prefusion intermediates. These prefusion intermediates are structures on the cell surface after viral attachment and receptor engagement but before fully functional viral entry. Using defined HIV prefusion DAGs, we have produced monoclonal antibodies (mAbs) specific to novel epitopes on HIV prefusion intermediates. These mAbs do not react with the static/native surface HIV or cellular antigens, but react with the DAGs. This is a paradigm shift from the current mainstream approach of screening elite patients' bNAbs. HIV: Designer antigens for elicitation of broadly neutralizing antibodies: Researchers have produced designer antigens that can elicit novel HIV antibodies which may have the potential to effectively prevent infection. The work, led by Tuckweng Kok and Peng Li at the University of Adelaide, Australia, exploited the fact that in rare cases HIV patients can produce neutralizing antibodies that bind to sites which exist only transiently as the virus fuses with cells. They created long‐lasting versions of these sites in a cellular model by lowering the temperature to arrest fusion midway through. This allowed time to produce antibodies that selectively bound to cells that were in the process of being infected, and potentially reduce the ability of HIV to infect cells. Previous attempts to make vaccines that produce broadly neutralizing antibodies in patients have failed. The new approach could help to produce broadly neutralizing antibodies or antiviral agents that reduce the risk of HIV transmission.